Grazing sequence pattern and species selection by cattle in the Dohne sourveld - Daines, Thomas (Rhodes University, Faculty of Science, Botany Department, 1976)
A detailed investigation into the harvesting of the standing grass crop within camps by cattle showed the following: 1. Cattle have a definite order of preference for the components of the Dohne Sourveld grass sward. The most palatable species in order of preference (based on Corrected Species Importance rating) are Themeda triandra, Tristachya hispida, Andropogon appendiculatus, Alloteropsis semialata and Heteropogon contortus. The least preferred species is Elionurus argenteus. 2. The key species, which is defined as the most abundant and productive palatable species, has been identified as Themeda triandra. 3. In harvesting the grass crop, cattle not only have a set preference for species, but also have a set grazing sequence pattern. This can be divided into three main phases. On entering the camp the animals first select the species of their choice, "creaming" these plants (grazed less than 50%) to obtain the most nutritious feed. In their daily search for food they spread their grazing over an increasingly wider area and over a wider range of species. When they can no longer obtain their daily requirements from this "creaming" operation of the more preferred species they return to the most preferred species , which are then heavily grazed (more than 50%) producing the common pattern of area grazing within a camp. These areas increase in size as the cattle graze down the species of their choice, moving to less preferred species as soon as they can no longer obtain their daily intake requirements from the more preferred species. Finally when they have no alternative they graze the least preferred species. 4. Increasing the stocking density does not alter the grazing sequence pattern or change the order of preference for the component species in the sward. It only increases the rate of utilization of the more preferred species and the various phases in the grazing sequence pattern are reached more rapidly. 5. At higher stocking densities the palatable species are more evenly utilized than at lower stocking densities. 6. Cattle graze a greater variety of species when the sward is young and actively growing. As the maturity of the sward increases the cattle concentrate on the more preferred species and are more selective in their grazing. However, their order of preference remains the same. Species that are highly preferred early in the season retain their ranking when the sward is mature. The only exception to this rule is Alloteropsis semialata. Early in the growing season this species is high on the preference list, but as it matures less is taken until when fully mature, it is rejected by cattle. 7. Elionurus argenteus is the least preferred of all the species in the Dohne Sourveld. Cattle will graze this plant as a last resort when grazing a camp early in the season, but reject the plant when it is fully mature. 8. To retain vigour and production of the Dohne Sourveld results of this investigation support the view that grazing management should be based on the principle of controlled selective grazing. Having shown that the more preferred species are over-utilized when attempting to utilize the least preferred species any grazing management that calls for total utilization of all standing vegetation should be rejected. 9. The results of this investigation supports a multicamp system for the Dohne Sourveld where high stocking densities are employed. This will result in the rapid and even utilization of the more preferred species. Management should be based on short period of stay and long period of absence. Cattle should be moved as soon as the key species have been well utilized, but not overgrazed. Cattle should only be returned to the camp when key species have made adequate regrowth following grazing. 10. A method, that is simple to use, is proposed for determining utilization of the veld and key species at different times of the year using the relationship between percentage of ungrazed plants and utilization of the sward and of Themeda triandra, the key grazing species in the sward. 11. Results show that when rested camps are grazed after May, the number of Themeda triandra inflorescences are drastically reduced. Veld that is specifically rested for the production of Themeda triandra seed should be rested from March of the year preceding expected seeding.
Keywords: Grasses -- Research -- South Africa -- Cape of Good Hope; Grasses -- South Africa -- Cape of Good Hope -- Identification; Grazing -- South Africa